Wood density and carbon content of mangrove species in Kuala Sepetang, Perak, Malaysia - M. R., Rabiatul Khairunnisa; Ismail, Mohd Hasmadi; Abdul Hamid, Hazandy (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Wood density and biomass of 13 mangrove species from the Matang mangrove reserve were studied to determine the variation in carbon stock. The determination of carbon content was carried out by a CHNS analyzer. From the study, the wood density range were 0.33 and 0.64 g/cm³ for Sonneratia caseolaris and Ceriops tagal, respectively. The carbon content for Bruguiera cylindrica and Lumnitzera racemosa were 40.14 and 45.13 %, respectively.